2020
DOI: 10.1016/j.jaut.2019.102357
|View full text |Cite
|
Sign up to set email alerts
|

Loss of epigenetic modifications on the inactive X chromosome and sex-biased gene expression profiles in B cells from NZB/W F1 mice with lupus-like disease

Abstract: The mechanisms underlying the female-bias in autoimmunity are poorly understood. The contribution of genetic and epigenetics factors from the inactive X chromosome (Xi) are beginning to emerge as critical mediators of autoimmunity in females. Here, we ask how epigenetic features of the Xi change during disease development in B cells from the NZB/W F1 spontaneous mouse model of lupus, which is female-biased. We find that Xist RNA becomes increasingly mislocalized from the Xi with disease onset. While NZB/W F1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…It was hypothesized that some genes on the inactive X chromosome (Xi) are predisposed to become partially reactivated in the naïve female lymphocytes [ 21 ]. However, examination of allelic expression of putative disease-causing candidate genes like Tlr7 failed to reveal major differences in biallelic cell frequencies between B cells from lupus-prone and wild-type mice [ 48 ]. Although the number of subjects was too low to draw any conclusions, no marked differences in TLR7 biallelic cell frequencies was also observed in EBV-B cells between SLE sufferers and healthy women [ 21 ].…”
Section: Role Of Xist Rna Localization On the XI In Aid?mentioning
confidence: 99%
“…It was hypothesized that some genes on the inactive X chromosome (Xi) are predisposed to become partially reactivated in the naïve female lymphocytes [ 21 ]. However, examination of allelic expression of putative disease-causing candidate genes like Tlr7 failed to reveal major differences in biallelic cell frequencies between B cells from lupus-prone and wild-type mice [ 48 ]. Although the number of subjects was too low to draw any conclusions, no marked differences in TLR7 biallelic cell frequencies was also observed in EBV-B cells between SLE sufferers and healthy women [ 21 ].…”
Section: Role Of Xist Rna Localization On the XI In Aid?mentioning
confidence: 99%
“…Genome-driven mouse models of lupus have been used to elucidate mechanisms of disease pathogenesis and to evaluate efficacy of interventions [5]. Similar to human lupus, female NZBWF1 mice are more likely to develop lupus than their male counterparts [6]. These mice display steady, gradual expansion of autoreactive B and T cells, proinflammatory cytokine and chemokine expression, elevations of autoantibodies, and development of organ damage, thus mimicking the periods of remission in human lupus that precede flaring.…”
Section: Introductionmentioning
confidence: 99%
“…Biallelic expression of Tlr7, ranging from 10 to 40% of cells, has also been recently observed in human B cells from healthy women, female SLE patients, as well as men with Kleinfelter syndrome [ 79 , 130 ]. Intriguingly, female lupus-prone NZB/W F1 mice also exhibit biallelic expression of Tlr7 that did not change with disease progression [ 131 •• ]. A polymorphism in the X-linked gene CXorf21 , an adaptor for endosomal TLRs including TLR7, is strongly associated with SLE in European populations [ 132 , 133 , 134 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro stimulation results in accumulation of both XIST RNA and heterochromatic marks on the Xi [ 80 , 136 ]. We recently found that in vitro activated T cells from human SLE patients and both T and B cells from late-stage disease NZB/W F1 mice have dispersed Xist RNA localization patterns [ 131 •• , 135 •• ]. In addition, T cells from SLE patients had altered expression of X-linked genes, including overexpression of genes involved in metabolism, cell cycle, and proliferation [ 135 •• ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation